The Effect of Nearpod-Based Learning Media on Students’ Learning Interest and Learning Outcomes - Anisa; Isnawati Lujeng Lestari (Universitas Islam Tribakti Lirboyo Kediri, 2026)
This study aims to develop a Nearpod-based mathematics learning media that is valid, practical, and effective in increasing the interest and learning outcomes of Grade X students at MA NU Lekok. The development model used is the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The instruments used in the research include expert validation sheets, practicality questionnaires, learning interest questionnaires, and pretest and posttest questions. The validation results from subject-matter and media experts indicated that the media falls into the